(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Underwater wireless sensor networks have received increased attention in recent years due to its numerous applications in oil spills detection, ocean exploration, submarine detection and disaster avoidance. All these applications make use of a number of sensor nodes deployed in different depths in the ocean for data collection and communication. Efficient communication in the network of sensor nodes requires a dynamic routing approach. In underwater routing protocols, there exist some partially state-full protocols which can guarantee the delivery of packets using excessive communication overhead. However, the design of Opportunistic routing protocols for UWSNs is challenging, due to the characteristics of the underwater acoustic channel. For instance, the high and variable delay, multipath propagation, low bandwidth, and high energy consumption render impractical the use of the up to date protocols developed for wireless sensor and mesh networks. In this paper, we presented the systematic review of different studies of opportunistic routing protocol for underwater sensor networks. The investigation and comparative analysis of recent studies related to the opportunistic routing protocols of the potentials and challenges of opportunistic routing in underwater sensor networks. The outcome of this paper claims the various research gaps identified from the literature review.